Kajian Etnobotani Tumbuhan yang Digunakan Sebagai Pewarna Alami Oleh Suku Dayak Iban Di Desa Mensiau Kabupaten Kapuas Hulu - Riza Linda, Epi Koryanti Santa, Mukarlina (Jurnal Protobiont, 2015)
Iban tribe is one of Dayak sub tribe spread in Borneo island, incluring West Borneo. Who utilize plenty of plants in their daily life. People of Dayak Iban tribe in Mensiau Village oftently utilize plants as natural dyes for strings that are to be used to make weaves of tradisional clothes, and also as natural dyes for foods. The of research was to cognize the species of plants used as natural dyes and now they are processed. This research was conducted in April to Juni 2014. The method of respondents selection used in this research was snowball method. The result showed that there are 5 species of plants used as natural dyes for strings and clothings, which are Morinda citrifolia, Psychoteria sp, Marsdenia tinctoria, Beting and Jangau. There are also 2 species of plants used as natural dyes for foods, which are Curcuma domestica and Pandanus sp.